Life to be lived : Challenges and choices for patients and carers in life-threatening illnesses. - Proot, Catherine; Yorke, Michael (Oxford : OUP Oxford, 2013)
How do people face life-limiting illness and death? This challenging question is discussed in-depth in Life to be Lived by looking at the feelings, hopes, fears and stresses associated with life-threatening illnesses, often experienced by patients and their carers. Drawn from research, clinical, and pastoral experiences, the authors examine the process of adjustment that patients and their families go through in major illnesses and when approaching the end of life. Life to be Lived is written in an accessible style using many stories shared by counsellors, chaplains, patients and relatives. De.
Part 5 The next step15 The next step?; The last great adventure; Grief and bereavement; In conclusion; Postscript; Index.
Print version record.
Includes bibliographical references and index.
WorldCat record variable field(s) change: 650
Keywords: Terminal care; Terminally ill -- Psychology; Bereavement; Hospice care; Terminal Care -- psychology; Terminal Care; Hospice Care; Bereavement; Soins en phase terminale; Malades en phase terminale -- Psychologie; Deuil; mourning; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Bereavement; Terminal care; Terminally ill -- Psychology; Electronic books; Electronic books